The EFFECT OF YOGA ON ENHANCEMENT OF BIOMARKER BETA-ENDORFINS IN THE AGING PROCESS : LITERATURE REVIEW - Tjahjono, Peter Djoko; Melati, Dikes; Marsabessy, Najmi Puspasari; Hartati, Tuti; Kurniawan, Nyoman Rama; Juhanna, Indira Vidiari; Adiatmika, I Putu (Sport and Fitness Journal; Vol 10 No 2 (2022): Volume 10, No. 2, May 2022, 2022)
The effect of  yoga in the increase in beta-endorphins biomarkers is the purpose of this literature review in the aging process. The method uses a database from Google Scholar, Researchgate and Mendeley. Search articles using keywords: yoga, sport, exercise, endorphins, anti-aging. Journals in English and Indonesian in the last 10 years have become our literature review material. The effect of yoga exercise intervention on the aging process (increase in one of the biomarkers, namely beta-endorphins) is obtained from 4 articles. What happens in the aging process is a decrease in functional capacity both at the cellular level and the loss of the ability to maintain body homeostasis, organ systems become dysfunctional and changes occur in the body. Essence; The physiological process of aging can be slowed down by doing yoga (endocrine, also cognitive, cardiovascular, musculoskeletal and immunological),changes in biomarkers, one of which is an increase in beta-endorphins,so that yoga will improve body functions including increasing heart rate, blood circulation, helping to provide oxygen, nutrients to the skin, increasing collagen production and keeping new cells glowing and for antiaging and a better quality of life. Limitations to the review are only research published in the last 10 years. The limitation of the method used is that there is no quality analysis and risk assessment of bias.   Keywords: yoga; sport; exercise; endorphins; anti-aging